Non-hormonal Clitoromegaly due to Clitoral Priapism Caused by Appendicitis/Appendectomy - BEREKET, ABDULLAH; DEMİRCİOĞLU, SERAP; GÜRAN, TÜLAY (My University, 2021)
Clitoromegaly usually develops due to hyperandrogenism. There are few cases of clitoromegaly described without clinical and biochemical hyperandrogenism. Clitoromegaly due to clitoral priapism and clitoral priapism after appendectomy have not been reported previously. A 7-year-old girl was referred for enlargement of the clitoris. She expressed having a mild, pulsating clitoral pain starting three days after an appendectomy operation. Subsequently, painful swelling and an increase in the size of the clitoris was observed. Her growth and physical examination were normal other than a clitoromegaly. The conditions related to androgen excess were excluded by comprehensive work-up. The color Doppler ultrasound revealed a high peak systolic velocity and resistance in the cavernosal artery consistent with clitoral priapism. The patient's complaints improved significantly with oral pseudoephedrine and intracavernosal aspiration. This unique case shows that clitoral priapism is a rare non-hormonal cause of clitoromegaly and can occur after appendectomy. Pseudoephedrine treatment is helpful in alleviating the symptoms.
Keywords: acute appendicitis; clitoral priapism; clitorism; Non-hormonal clitoromegaly; pelvic inflammation